Inclusive educational practices in Kenya: Evidencing practice of itinerant teachers who work with children with visual impairment in local mainstream schools - Lynch, Paul; McCall, Steve; Douglas, Graeme; McLinden, Mike; Mogesa, Bernard; Mwaura, Martha; Muga, John; Njoroge, Michael (International Journal of Educational Development, 2011)
This article presents a findings from an investigation of the work of 38 specialist itinerant teachers (ITs) supporting the educational inclusion of children with visual impairment in Kenya. The research was designed around a participatory action research framework involving in-country researchers and participants (teachers) working in collaboration with researchers in the United Kingdom. Following an introductory training workshop, participants kept research journals over a 2-month period in which they recorded details of their itinerant duties (including the processes and content of their visits). Findings provide information about local practices of ITs support for children with visual impairment in mainstream schools and raise broader questions about the barriers to learning and development facing children with disabilities in mainstream schools in Kenya and other developing countries.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2010.08.006 2339240:99E5PNBZ 2405685:F3M4BRIW
Keywords: Inclusive education; Itinerant teachers; Kenya; Participatory action research; Visual impairment

Developing a systemic approach to teacher education in sub-Saharan Africa: emerging lessons from Kenya, Tanzania and Uganda - Hardman, Frank; Ackers, Jim; Abrishamian, Niki; O’Sullivan, Margo (Compare: A Journal of Comparative and International Education, 2011)
While many countries in Eastern and Southern Africa are on track for meeting the Education for All targets, there is a growing recognition of the need to improve the quality of basic education and that a focus on pedagogy and its training implications needs to be at the heart of this commitment. By drawing on three East African countries, Kenya, Tanzania and Uganda, which are at different stages of development with regard to the reforming of teacher education, this paper explores the challenges and the lessons learned from each of the countries with regard to the development and strengthening of pre- and in-service training. The tension between quality, breadth and cost-effectiveness is explored together with a broader discussion of key principles to be taken into account when enhancing teacher education in the region as a whole.
shortDOI: 10/gftr63 KerkoCite.ItemAlsoKnownAs: 10.1080/03057925.2011.581014 10/gftr63 2339240:7KFNHLPK 2339240:I6BDIQNZ 2339240:JJ5GL8XB 2339240:LE5N7BCQ 2405685:CBBDLLFH 2405685:J57J3RGT 2405685:PDZKWSFZ 2405685:Q7GP9QSC 2405685:QWHDI7ZH 2534378:L9VFMLYK
Keywords: C:Kenya / Uganda / Tanzania; Education; Education for All; Education reform; Kenya; Pedagogy; Principles; Quality of education; Tanzania; Teacher education; Uganda; ___working_potential_duplicate; basic education; pre-service and in-service training; quality education; sub-Saharan Africa; teacher education reform

Learning English Language by Radio in Primary Schools in Kenya - Odera, Florence (2011)
Learning English Language by Radio in Primary Schools in Kenya By Florence Y. Odera (PhD) P.O.Box 2303, Kisumu, Kenya Introduction and background information One of the
KerkoCite.ItemAlsoKnownAs: 2339240:H2WW7AHK 2405685:AI2IS3MP
Keywords: ___working_potential_duplicate

GIS in Education Planning: The Kenyan School Mapping Project - Mulaku, G.C.; Nyadimo, E. (Survey Review, 2011)
School mapping consists of the building of geospatial databases of educational, demographic and socioeconomic data for educational institutions in order to support educational planning and decision making. Such databases contain data such as the geographic location of schools, the numbers of existing schools of different levels in the public and private sectors, their capacities, physical condition and facilities, enrolment and the number of teachers and their attributes. Also often included are data on related natural features and infrastructure such as rivers, roads, economic and administrative centers, medical facilities, religious facilities, etc. This paper describes the Kenyan School Mapping Project, whose objective was to collect such data for all Kenyan learning institutions and to integrate them in a GIS database that could be queried to provide useful information for educational planners, other professional users and average citizens. Results show that at the time of the project, there were nearly 73000 learning institutions in Kenya, ranging from early childhood schools to universities; useful information products on important educational indicators such as schools distribution, enrolments, pupil-teacher ratios and gender parity indices have also been generated from GIS analysis of the data. These results have demonstrated the utility of the database for its stated purpose and therefore shown the project to be a useful model that can be emulated by other developing countries.
Publisher: Taylor & Francis _eprint: https://doi.org/10.1179/003962611X13117748892155 KerkoCite.ItemAlsoKnownAs: 10.1179/003962611X13117748892155 2405685:HH3GP4V2 4042040:NJ6E8C3M
Keywords: EMIS; GIS; KENYA; SCHOOL MAPPING

The Effect of Computer-Assisted Instruction on Student’s Attitudes and Achievement in Matrices and Transformations in Secondary Schools in Uasin Gishu District, Kenya - Mwei, Philip K.; Too, Jackson K.; Wando, Dave (2011)
Performance in Mathematics in secondary school Education in Kenya remains poor. Consequently the Kenya secondary school examination (KCSE) Mathematics results continue to cause concern to all the stakeholders in the education sector. Therefore, there is serious and urgent need for intervention. Although research has indicated that computer-assisted instruction (CAI) enhances student achievement, promotes positive attitudes towards Mathematics and instruction, and improves interpersonal relations, few studies have focused on CAI in Kenyan secondary schools Mathematics teaching/learning. The purpose of this study was to investigate the effects of CAI on students’ attitude and achievement in matrices and transformations between form four students who received instruction using CAI module or conventional instruction methods. The pretest – posttest control group experimental research design was used. Six classes selected at random with 205 students participated in the study. Results of this study indicated higher achievement and positive attitudes with CAI treatment groups. Making connections between the goals of Mathematics education and CAI offers a valuable means for improving mathematical knowledge and skills and hence performance in Mathematics.
Accepted: 2020-04-29T08:24:24Z Publisher: World Council for Curriculum Instruction KerkoCite.ItemAlsoKnownAs: 2339240:6I5FF3K4 2405685:6SE7SU4R
Keywords: ⛔ No DOI found

Peer Effects, Teacher Incentives, and the Impact of Tracking: Evidence from a Randomized Evaluation in Kenya - Duflo, Esther; Dupas, Pascaline; Kremer, Michael (American Economic Review, 2011)
To the extent that students benefit from high-achieving peers, tracking will help strong students and hurt weak ones. However, all students may benefit if tracking allows teachers to better tailor their instruction level. Lower-achieving pupils are particularly likely to benefit from tracking when teachers have incentives to teach to the top of the distribution. We propose a simple model nesting these effects and test its implications in a randomized tracking experiment conducted with 121 primary schools in Kenya. While the direct effect of high-achieving peers is positive, tracking benefited lower-achieving pupils indirectly by allowing teachers to teach to their level. (JEL I21, J45, O15)
KerkoCite.ItemAlsoKnownAs: 10.1257/aer.101.5.1739 2339240:W5VT6F6A 2405685:98PTSC94
Keywords: Analysis of Education; Public Sector Labor Markets; Economic Development: Human Resources; Human Development; Income Distribution; Migration